Komunikasi Berkualitas: Solusi Meningkatkan Kepercayaan dalam Hubungan Long Distance Marriage (LDM) - Yulita Yunggu; Yoshevania Joyce Tandiari; Zakina Azzahra Zukri; Zuleyka Nurul Azkiya (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2026)
This study is motivated by the importance of communication in Long Distance Marriage (LDM), where direct interaction is limited. This study aims to examine the role of communication in building and maintaining trust among LDM couples. The method used is a Systematic Literature Review (SLR) based on PRISMA guidelines. Data were collected from journal articles published between 2016–2026 through Google Scholar, Scopus, and ScienceDirect databases with predefined inclusion and exclusion criteria. The results indicate that communication plays an important role in maintaining the quality of relationships among LDM couples. Several findings show that effective communication, openness, and communication intensity are related to trust, commitment, and relationship harmony. In addition, the use of communication media helps couples maintain emotional closeness. In conclusion, communication is an important factor in supporting relationship sustainability and building trust in LDM couples.